2006
DOI: 10.1111/j.1469-0691.2005.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of a dominant methicillin-resistant Staphylococcus aureus (MRSA) clone in a Mexican hospital (1999–2003)

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) isolates (n = 216), collected between January 1999 and May 2003 in a tertiary-care university hospital in Guadalajara, Mexico, were characterised by antibiotype, pulsed-field gel electrophoresis (PFGE) of SmaI macrorestriction fragments, and hybridisation of ClaI digests with mecA- and Tn554-specific DNA probes. Representatives of the single clonal type found were analysed by spa typing, multilocus sequence typing and staphylococcal chromosomal cassette mec (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
1
10
1
1
Order By: Relevance
“…Results given by trimethoprim-sulfamethoxazole are even worse with a mere 33.8% susceptibility in the current study, 21.1% from Bukharie and Abdelhadi[28], 2001 and full resistance by Panhotra et al, 2005[48]. Our results are in sharp contrast with those of Echa'niz-Aviles et al[53], 2006 who found all their isolates to be susceptible to gentamicin and trimethoprim-sulphamethoxazole. It is pertinent to deduce that antibiotics such as gentamicin and trimethoprim-sulfamethoxazole and the local fusidic acid should no longer be relied upon at least for empirical treatment of the local MRSA isolates.…”
Section: Resultscontrasting
confidence: 89%
“…Results given by trimethoprim-sulfamethoxazole are even worse with a mere 33.8% susceptibility in the current study, 21.1% from Bukharie and Abdelhadi[28], 2001 and full resistance by Panhotra et al, 2005[48]. Our results are in sharp contrast with those of Echa'niz-Aviles et al[53], 2006 who found all their isolates to be susceptible to gentamicin and trimethoprim-sulphamethoxazole. It is pertinent to deduce that antibiotics such as gentamicin and trimethoprim-sulfamethoxazole and the local fusidic acid should no longer be relied upon at least for empirical treatment of the local MRSA isolates.…”
Section: Resultscontrasting
confidence: 89%
“…Here we are comparing two different environments with different features that could determine the preference for colonization of each particular strain. Isolation of MRSA strains from hospitals in Mexico has been reported (4,12). The percentage of MRSA strains reported by Calderón-Jaimes et al (4) isolated from hospitals in Mexico City was 14.2% between 1998 and 2000.…”
Section: Discussionmentioning
confidence: 99%
“…ST5 appeared almost simultaneously in 11 counties, whereas ST228 was first isolated in the restricted area of Budapest, and only spread later throughout the country. Interestingly, to our knowledge, the New York/Japan clone has never been described in countries bordering Hungary, and was therefore probably imported from countries in which it is highly prevalent, i.e., the USA, Japan, Korea and Mexico [37–39]. Nevertheless, clone ST5‐II has been reported recently in some Belgium hospitals, as was the ST45‐IV clone, which was predominant among 251 isolates recovered from 95 hospitals during 2003 [40].…”
Section: Discussionmentioning
confidence: 99%